2018
DOI: 10.1103/physreve.97.062124
|View full text |Cite
|
Sign up to set email alerts
|

Stokes-Einstein relation of the liquid metal rubidium and its relationship to changes in the microscopic dynamics with increasing temperature

Abstract: For liquid rubidium the Stokes-Einstein (SE) relation is well fulfilled near the melting point with an effective hydrodynamic diameter, which agrees well with a value from structural investigations. A wealth of thermodynamic and microscopic data exists for a wide range of temperatures for liquid rubidium and hence it represents a good test bed to challenge the SE relation with rising temperature from an experimental point of view. We performed classical molecular dynamics simulations to complement the existing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…Interestingly, this change is close to a temperature , which was derived as a thermodynamic stability limit of the solid crystalline state of aluminium 31 , and beyond which no superheated metastable solid aluminium may survive.. That temperature agrees well with the increase in the amplitude , which is a measure for the decay of density fluctuations on next-neighbor distances. The amplitude can be related directly to an average relaxation time for the density fluctuations 33 and hence evidences a slowing down of the dynamics.
Figure 3 The relaxation times from the KWW-fits to the simulation and X-ray data are plotted against the inverse temperature on a logarithmic scale.
…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, this change is close to a temperature , which was derived as a thermodynamic stability limit of the solid crystalline state of aluminium 31 , and beyond which no superheated metastable solid aluminium may survive.. That temperature agrees well with the increase in the amplitude , which is a measure for the decay of density fluctuations on next-neighbor distances. The amplitude can be related directly to an average relaxation time for the density fluctuations 33 and hence evidences a slowing down of the dynamics.
Figure 3 The relaxation times from the KWW-fits to the simulation and X-ray data are plotted against the inverse temperature on a logarithmic scale.
…”
Section: Resultsmentioning
confidence: 99%
“…For monatomic liquid metals changes with temperature were found in the structural relaxation dynamics on an atomistic length scale for rubidium, lead, and aluminium [8][9][10]. The amplitude S(Q 0 , ω = 0) of the collective dynamics at the structure factor maximum Q 0 showed in all three cases a change in the slope in a similar temperature range above the * franz.demmel@stfc.ac.uk melting temperature [11]. Furthermore, for all three metals an increase of the generalized longitudinal viscosity was demonstrated which occurs in a temperature range of 1.3-1.5 T m upon cooling, suggesting that the liquid metals become more viscous around this temperature range.…”
Section: Introductionmentioning
confidence: 92%
“…These changes are based on fluctuations on an atomic length scale. However, recently the scrutiny of macroscopic transport coefficients of liquid rubidium and their product, the Stokes-Einstein relation, suggested that the change in dynamics also shows some fingerprints in the macroscopic transport parameters [56]. Furthermore the evolution of excitations with rising temperature indicated a change in collective particle dynamics in that temperature range [57].…”
Section: Introductionmentioning
confidence: 99%